1999
DOI: 10.1074/jbc.274.3.1856
|View full text |Cite
|
Sign up to set email alerts
|

Translocation-arrested Apolipoprotein B Evades Proteasome Degradation via a Sterol-sensitive Block in Ubiquitin Conjugation

Abstract: In this study, we explored how sterol metabolism altered by the expression of cholesterol-7␣-hydroxylase NADPH:oxygen oxidoreductase (7␣-hydroxylase) affects the ubiquitin-dependent proteasome degradation of translocation-arrested apoB53 in Chinese hamster ovary cells. Stable expression of two different plasmids that encode either rat or human 7␣-hydroxylase inhibited the ubiquitin conjugation of apoB and its subsequent degradation by the proteasome. Oxysterols (25-hydroxycholesterol and 7-ketocholesterol) rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…Our findings are the first to show that in vivo deletion of MTP function (either by Cre -mediated gene disruption or chemical inhibition) blocked hepatic secretion of apoB-100 without causing apoB to accumulate in the ER. These findings are consistent with the notion that while loss of MTP function blocks apoB translocation, apoB does not accumulate in the ER (21,25,(43)(44)(45) because it is cotranslationally degraded (30,37,46,47). Our finding that interruption of MTP function results in the rapid and efficient degradation of secretionincompetent apoB in vivo explains why apoB does not ac- cumulate in hepatic ER.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are the first to show that in vivo deletion of MTP function (either by Cre -mediated gene disruption or chemical inhibition) blocked hepatic secretion of apoB-100 without causing apoB to accumulate in the ER. These findings are consistent with the notion that while loss of MTP function blocks apoB translocation, apoB does not accumulate in the ER (21,25,(43)(44)(45) because it is cotranslationally degraded (30,37,46,47). Our finding that interruption of MTP function results in the rapid and efficient degradation of secretionincompetent apoB in vivo explains why apoB does not ac- cumulate in hepatic ER.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, two other agents, ␤ CD and apoA-I, were also used to remove rather than deliver cholesterol to the HepG2 cells, and these produced the same effect on bile acid synthesis as HDL3. With regard to apoB-100 metabolism, in CHO cells expressing apoB53, but not MTP, cholesterol 7 ␣ -hydroxylase protected against conjugation of the translocation arrested apoB53 with ubiquitin, and therefore reduced proteosome mediated degradation (22). On this basis, Davis has suggested that there is a direct relation between cholesterol 7 ␣ -hydroxylase activity and apoB-100 secretion and that this explains the increased hepatic triglyceride secretion in familial hypertriglyceridemia (23).…”
Section: Discussionmentioning
confidence: 99%
“…Properties of the ER membrane subject to possible alteration by oxysterols may include the width, fluidity, packing density, or protein density of the ER membrane. The observation that oxysterols, under certain genetic conditions, affect the stability and cellular localization of several membrane proteins not related to HMGR provides modest evidence for such a possibility (52).…”
Section: Discussionmentioning
confidence: 99%